Visual Hybridity: Margaret Murray Cookesley’s Orientalist Aestheticism - Julia Kuehn (Cahiers Victoriens et Edouardiens)
This essay foregrounds the work of late nineteenth-century British painter Margaret Murray Cookesley, who may be largely forgotten today, but who in her day exhibited regularly at the Royal Academy and, it seems, also managed to sell her art to an interested public. What makes her oeuvre fascinating in the context of British Aestheticism is that she successfully combined artistic principles adopted from the Aesthetic Movement with the Eastern subject matter inherited from the Orientalist painting tradition. By analysing a number of Cookesley’s Orientalist-Aestheticist paintings of harem women this essay thus suggests that Aestheticism was by no means a well-defined or self-contained artistic movement but was open enough to invite often bizarre hybrids like Cookesley’s works into its circle.